Case study on effects of the mandatory validation on bus commercial speed - Pronello, Cristina; Gaborieau, Jean-Baptiste; Rappazzo, Valentina; Operti, Valerio (European Journal of Transport and Infrastructure Research, 2019)
The paper aims to define the new operational requirements and procedures to allow the Gruppo Torinese Trasporti (Torino public transport company) to implement mandatory validation without negative impacts on both the company and the users. To this end, a four-step methodology has been put forward: a) choice of the reference route; b) sampling plan and data collection; c) data analysis design and model specification and d) definition and analysis of future scenarios. Attained results show an increase of commercial speed from 1.5% to 14.5%, and an increase of the proportion of total dwell time on total trip time from 1 to 13 points. The most unfavourable situation for the company would be banning people from boarding the bus/tram through any door (the case today). Indeed, it would require an increase of trips in the morning peak hour in order to maintain the same time interval at bus stops. However, the impact on passengers’ travel time is non negligible since total vehicle trip time shows a rise of up to 10 minutes during weekends shifts (from 62 minutes in the current situation to 72 minutes for the worst case scenario). Thus, the present system limits the outcomes negatively for the users in terms of waiting time. However, a change could lead to such positive consequences as fuller passenger cooperation to validate tickets/passes and a more ordered boarding, thus reducing fraud and improving the image of the company.